Virtual Pilgrimage in a Time of Pandemic: Lessons from the Shrine of Our Lady of Walsingham - Susan Dunn-Hensley (International Journal of Religious Tourism and Pilgrimage)
The COVID-19 pandemic has already cost billions to those in the tourist industry. According to the United Nations World Tourism Organization (UNWTO), this pandemic is ‘by far the worst crisis that international tourism has faced since records began’ in 1950. People who rely on the pilgrim trade are similarly suffering. In this short exploration, I argue that the success of virtual pilgrimage and the history of pilgrimage’s adaptability suggest that people’s appetite for pilgrimage will experience a resurgence once local and national governments lift travel restrictions. In order to assess the future of pilgrimage, I will consider the popularity of virtual pilgrimage (including participation in virtual walks and viewing of religious rituals online). I will use history as evidence, arguing that pilgrimage has shown a remarkable ability to adapt to changing circumstances including plague and war, and that virtual pilgrimage is not a new concept. I will focus in particular on the Shrine of Our Lady of Walsingham, arguing that, if virtual interest in the Shrine gives us any indication, pilgrimage will recover despite the strains placed on it by the pandemic. More importantly, however, the experience of virtual pilgrimage might actually add a new and exciting component of inclusion to traditional pilgrimage.